ANALYSIS THE EFFECT OF CAMSHAFT WITH LSA 244,5° AND ECU REMAP ON PERFORMANCE AND EXHAUST GASES ON BBS1 TYPE ENGINE (Universitas Pendidikan Indonesia, 2025)
Good engine performance is very important for people who like to travel long distances or touring on their motorbikes. . In an effort to improve engine performance, there are several steps that can be taken, namely changing or modifying the camshaft in the valve system. The aim of this research is to analyze the effect of using a camshaft with a larger LSA on the performance of BBS1 motorbikes and to determine the effect of ECU re-map on power, torque and fuel consumption on BBS1 motorbikes. This research was carried out experimentally through testing using a dynotest. For this test, a Yamaha The research results show that the use of LSA 244,5° camshaft variations and ECU re-map can increase torque power, but increases fuel consumption.